Evolution of the volatile flavor compounds of Chinese horse bean-chili-paste. (March 2019) - Lu, Yunhao; Chi, Yuanlong; Lv, Yuanping; Yang, Guohua; He, Qiang
Abstract: The production of Chinese horse bean-chili-paste (CHCP) involves three fermentation phases: a chili-to-moromi phase, a horse bean-to-meju phase and a moromi-meju mixed fermentation phase. In consideration of raw materials and fermentation phases, the evolution of key volatile flavor compounds in CHCP were investigated in this study by using GC-MS, olfactometry and principal component analysis. Results showed that there were 22 key flavor compounds in CHCP. Among which, ( E )-2-nonenal, nonanal and 3-methyl-1-butanol were primarily from chili, and 1-octen-3-ol was from horse bean. Ethyl decanoate and linalool were mainly formed during the chili fermentation, while ethyl isobutyrate, phenylethyl alcohol and benzene acetaldehyde were found closely related to the horse bean-to-meju process. The mixed fermentation of chili moromi and horse bean meju was significant for the accumulation of 13 key compounds, including 2-methyl-1-butanol, 3-methyl butyraldehyde, 2-methyl butyraldehyde, ethyl isovalerate, ethyl hexanoate, ethyl benzoate, ethyl phenylacetate, guaiacol, 4-ethyl phenol, 4-ethyl guaiacol, 4-hydroxy-2, 5-dimethyl-3(2H)-furanone (HDMF), 4-hydroxy-2(or 5)-ethyl-5(or 2)-methyl-3(2H)-furanone (HEMF) and 3-(methylthio) propanal. Results are conducive to understand the accumulation mechanism of CHCP flavor compounds and promote the quality improvement. Highlights: The key flavor compounds of Chinese horse bean-chili-paste (CHCP) were identified. Evolution of the flavor compounds was first investigated in CHCP production. Most of key flavor compounds were found accumulating in mixed fermentation phase. Knowing flavor compounds' accumulation mechanism benefits CHCP quality improvement.